TRANSLATION AND VALIDATION OF A TURKISH VERSION OF THE CALIFORNIA CRITICAL THINKING DISPOSITION INVENTORY - Iskifoglu, Gokhan; Agazade, Ali Sidki (Soc Personality Res Inc, 2013)
In this study, we translated into Turkish and carried out a validation process of the California Critical Thinking Disposition Inventory (CCTDI; Facione, 1990), a multidimensional inventory of students' evaluation of critical thinking dispositions. The goals were to translate the CCTDI into Turkish, assess the psychometric properties, and examine the factorial validity of the hypothesized 7-factor model through confirmatory factor analysis, with a view to using this instrument for assessment in teacher education programs in Turkey. Based on data from 583 Turkish university students, the translated Turkish version of the CCTDI displayed positive psychometric properties, thus supporting the applicability of the CCTDI in the Turkish educational context. However, analysis of the factorial structure produced a poor fit of the hypothesized multidimensional model of the CCTDI to the observed data. The results of further analysis, based on the modification indices, provided support for the use, for cross-cultural comparison, of a 4-factor model with a reduced number of items.
Keywords: California Critical Thinking Disposition Inventory; Turkish translation; validity; psychometric properties; critical thinking disposition; teacher education program; Turkey